2014
DOI: 10.1164/rccm.201404-0689oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-26 in Antibacterial Host Defense of Human Lungs. Effects on Neutrophil Mobilization

Abstract: This study implies that alveolar macrophages produce IL-26, which stimulates receptors on neutrophils and focuses their mobilization toward bacteria and accumulated immune cells in human lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
139
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(150 citation statements)
references
References 44 publications
10
139
1
Order By: Relevance
“…We also demonstrated that IL-26 enhances the chemotactic response of neutrophils toward a bacterial stimulus and toward IL-8, while at the same time inhibiting the chemokinesis in these innate effector cells (9)(10)(11). Moreover, we demonstrated that alveolar macrophages constitute a prominent source of IL-26, in addition to Th17 cells and other lymphocyte subsets.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…We also demonstrated that IL-26 enhances the chemotactic response of neutrophils toward a bacterial stimulus and toward IL-8, while at the same time inhibiting the chemokinesis in these innate effector cells (9)(10)(11). Moreover, we demonstrated that alveolar macrophages constitute a prominent source of IL-26, in addition to Th17 cells and other lymphocyte subsets.…”
mentioning
confidence: 54%
“…Given the abundance of IL-26 protein in the human airway lumen and its referred involvement in the immune response to bacterial (9,10) and viral stimulation (7,12,13), we hypothesized that IL-26 is involved in pulmonary host defense against viruses by being produced in bronchial epithelial cells after stimulation with a viral stimulus and that this production is modulated by additional Th17 cytokines. We also hypothesized that the intracellular signaling pathways leading to IL-26 release involves mitogen-activated protein (MAP) kinases and the nuclear transcription factor NF-κB.…”
Section: Interleukin-26 Production In Human Primary Bronchial Epithelmentioning
confidence: 99%
See 3 more Smart Citations